Impact of resilience enhancing programs on youth surviving the Beslan school siege - Gallo William T; Henley Robert R; Mueller Mario; Dulaev Igor; Vetter Stefan; Kanukova Zalina (BMC, 2010)
Abstract The objective of this study was to evaluate a resilience-enhancing program for youth (mean age = 13.32 years) from Beslan, North Ossetia, in the Russian Federation. The program, offered in the summer of 2006, combined recreation, sport, and psychosocial rehabilitation activities for 94 participants, 46 of who were taken hostage in the 2004 school tragedy and experienced those events first hand. Self-reported resilience, as measured by the CD-RISC, was compared within subjects at the study baseline and at two follow-up assessments: immediately after the program and 6 months later. We also compared changes in resilience levels across groups that differed in their traumatic experiences. The results indicate a significant intra-participant mean increase in resilience at both follow-up assessments, and greater self-reported improvements in resilience processes for participants who experienced more trauma events.